Plano diretor sem política pública, políticas sem planejamento urbano: análise do Plano Diretor Participativo de Fortaleza como ordenador da política pública urbana - Cabral, Camila Rodrigues (2024)
Understanding that public policy and urban planning are inextricably linked, the research examines their interaction. Numerous authors have already conducted analyses of the participatory formulation process and the implementation of the instruments on the territory following two decades of Brazilian urban legislation, Estatuto da Cidade, which regulates the mandatory production of municipal urban Master Plans. The possibility of having to evaluate this plan again, however, highlights the necessity of a continuous research agenda on the function of urban planning in public policies as well as an awareness of the Master Plan's role in order to proceed with finding the gaps in the planning analysis. The main component of the study technique is a bibliographical review of Brazilian urban public policy, with a focus on the relationship between urban planning and the creation of urban space. Therefore, the research presents the city of Fortaleza with the implementation of its Participatory Master Plan in order to analyze the correlations and gaps between the urban policy guidelines present in the Master Plan and the implementation of sectoral urban public policies. The analysis systematically identifies fiscal, spatial, normative, and institutional axes based on instances of pertinent programs during the time of 2010-2021. The systemic evaluation of the instruments' implementation and the guidelines' reflection in the urban public policy implementation during the evaluated period allow for a more efficient and integrated approach within the plan's scope, given the temporal end of the execution cycle and the start of the review process